Design and Implementation of an IoT Ready Smart Sensor for Speed Sensing of a DC Motor using IEEE 802.15.1 and ESP8266 - Jain, Ankur; K. Roy, B (International Journal of Engineering and Technology, 2018)
An IoT enabled smart sensor for speed sensing of a DC motor is designed and implemented. This is a generic platform enabled with Wi-Fi, Bluetooth, etc. It can also be used for many other applications.Â  In this paper, we have used cyber-physical aspects for the co-design of hardware and software. Our design is equipped with Bluetooth radio frequency link and TCP/IP stack. The sensor node is able to communicate to both near and far range according to the requirement. IP addresses make it uniquely identifiable. Implementation is done as per the layered architecture which makes it interoperable. A demo setup is made for veriï¬cation.Â Â